The new kids on the block of arrhythmogenic disorders: Short QT syndrome and early repolarization. (27th June 2017) - Mazzanti, Andrea; Underwood, Katherine; Nevelev, Dmitriy; Kofman, Shanna; Priori, Silvia G.
Abstract: Short QT syndrome (SQTS) is one of the rarest inheritable cardiac channelopathies, characterized by an accelerated cardiac repolarization, which is also the substrate for the development of life‐threatening ventricular arrhythmias. Up to this date, fewer than 200 SQTS cases have been reported in the literature worldwide. Patients with SQTS may experience a cardiac arrest as early as in the neonatal period or as late as 80 years old. The cumulative probability of experiencing a cardiac arrest by the fifth decade of life approaches 40%, highlighting the importance of early recognition and management. SQTS is an autosomal dominant disease with five identified causative genes, including three that encode for potassium channels ( KCNH2, KCNQ1, and KCNJ2 ) and two that encode for subunits of the L‐type calcium channels ( CACNA1C and CACNB2 ). The term "early repolarization" (ER) has long been used to refer to a heterogeneous group of specific QRS‐T junction patterns that are commonly found on the electrocardiograms of young healthy subjects. In the last decade, it has been suggested that in some individuals, the presence of ER may be associated with an increased risk of sudden cardiac death, and thus the term "early repolarization syndrome" (ERS) has progressively entered into use. Up to this point, however, whether ER constitutes a true primary arrhythmic disorder or whether it is simply a predisposing substrate that facilitates arrhythmias in the presence of other triggers remains an unresolved issue. In this review paper, we aim to integrate the current literature on SQTS and ERS. For each, we will describe the key steps that first led to the identification of the syndrome before moving into a discussion of our current understanding of each entity, including the epidemiology, genetics, diagnosis, clinical manifestations, and management.